2011
DOI: 10.1097/sla.0b013e318211caf8
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Administration Via the Portal Vein Promotes Liver Regeneration in Rats After 70% Hepatectomy

Abstract: Platelets infused via the portal vein promoted liver regeneration after 70% hepatectomy in rats without liver damage. These findings indicate that PRP administration could be a useful part of liver regeneration therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 21 publications
(36 reference statements)
5
85
0
Order By: Relevance
“…This notion is supported by preclinical studies reporting a central role of platelets on liver regeneration after hepatectomy in mice [6,7]. Indeed, most of the relevant growth factors for liver regeneration are stored in platelets [8,9] and direct application of platelet-rich plasma via the portal vein accelerates postoperative liver regeneration in rodents [10].…”
supporting
confidence: 55%
“…This notion is supported by preclinical studies reporting a central role of platelets on liver regeneration after hepatectomy in mice [6,7]. Indeed, most of the relevant growth factors for liver regeneration are stored in platelets [8,9] and direct application of platelet-rich plasma via the portal vein accelerates postoperative liver regeneration in rodents [10].…”
supporting
confidence: 55%
“…In our previous studies, we revealed that platelets play a crucial role in promoting liver regeneration. [6][7][8][9] Platelets (anuclear blood cells) are derived from megakaryocytes (MKs), which contain not only proteins needed for hemostasis but also many growth factors that are required for tissue regeneration and repair. 10 We also reported that platelets have a preventive effect on the progression of liver fibrosis in vitro and in vivo and that the increase in platelets induced by platelet transfusion can improve the liver function of patients with CLD and cirrhosis in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been well established that platelets are vital for liver regeneration after a partial liver resection in animals. [10][11][12][13][14][15] Significantly, liver regeneration after partial liver resection was shown to be substantially delayed in mice that were treated with drugs that inhibit platelet function or in mice with thrombocytopenia induced by chemotherapeutic drugs or platelet-depleting antibodies. 10 Conversely, mice in which the platelet count was increased by treatment with thrombopoietin receptor agonists or by administration of platelet concentrates showed accelerated liver regeneration.…”
Section: Evidence For a Stimulatory Role Of Platelets In Liver Regenementioning
confidence: 99%
“…10 Conversely, mice in which the platelet count was increased by treatment with thrombopoietin receptor agonists or by administration of platelet concentrates showed accelerated liver regeneration. [13][14][15] In addition to the role of platelets in regeneration following a partial hepatectomy, it has been established that platelets delay fibrosis in animal models of chronic intoxication 16,17 and that platelets facilitate repair after ischemia/reperfusion injury. 18 However, studies have also identified detrimental effects of platelets following these insults.…”
Section: Evidence For a Stimulatory Role Of Platelets In Liver Regenementioning
confidence: 99%